MRI from A to Z a definitive guide for medical professionals - Liney, Gary.; SpringerLink (Online service). (London New York Springer-Verlag, 2010)
This second edition of Gary Liney?s MRI from A-Z, much expanded from the first edition, is both a reflection of and an apt companion for the dramatic growth in the field of MRI. The MRI trainee and the extensively experienced MRI practitioner alike will find this A-Z of the field, with 1,300 entries and 100 illustrations, to be an indispensable reference tool. Providing the reader with concise, clear and eloquent definitions of MRI terminology, this book is both highly practical and a pleasure to read. Gary Liney, PhD is the Principal Physicist for Oncology Imaging and Radiotherapy Physics at the Queen?s Centre for Oncology, Castle Hill Hospital, Cottingham, UK.
Electronic reproduction.
Keywords: Magnetic resonance imaging; Electronic books